Good governance based on service information system applications administration population via smartphones - Malawat, Sitna Hajar; Merdayanty, Dewi; Junaidy, Junaidy; Shaddiq, Syahrial (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Good Governance aims to encourage efficient management, openness, active participation, and fairness in the organizational or governmental structure. If applied to an application platform that manages population administration services, the principles of Good Governance can secure the smooth running of these services, in line with the needs of the community. The purpose of the study was to determine the implementation of Good Governance based on an information system application for population administration services via smartphones in Tanah Laut Regency and the obstacles in its implementation which have become part of the governance of the Indonesian state in general and specifically in the Department of Population and Civil Registration of Tanah Laut Regency. The data analysis technique is to use interactive model data analysis (data reduction). The results show that the context of the principles of Good Governance at the Department of Population and Civil Registration of Tanah Laut Regency still needs to be improved again, this is because there are still some principles that are still not running optimally, such as the presence of individuals who prioritize the interests of groups/officials, lacking facilities and infrastructure, such our computers and there are employees who are not under their competence.